Logística 4.0 e sustentabilidade: análise das práticas, benefícios e desafios em prestadores de serviços logísticos - Rodrigues, Nayra Vasiulis Ferreira (Universidade Federal de São Carlos, 2023)
Logistics 4.0 involves optimizing logistical activities through the use of intelligent systems, enhancing analytical and operational capabilities, and providing sustainable solutions. The overall objective of this research is to analyze how the adoption of Logistics 4.0 can promote sustainability in the activities of Logistics Service Providers (PSL). To achieve this, a systematic literature review (SLR), a multiple case study with five Brazilian PSLs, and complementary interviews with seven experts in logistics and sustainability applied to logistics services were conducted. The data were analyzed using content analysis with NVivo software support. The main findings of this study demonstrate that Logistics 4.0 can support PSLs in developing sustainable processes and business models through process automation, real-time monitoring, and system integration. In the transportation sector, Logistics 4.0 technologies are being utilized for route planning, vehicle parameter monitoring, and cargo tracking throughout the transportation process. Additionally, in intralogistics, Logistics 4.0 technologies are applied in managing and monitoring material movement and real-time inventory parameters, as well as automating repetitive tasks, resulting in increased efficiency and error reduction. It was observed that these technologies generate social, environmental, and economic benefits, including improved energy efficiency, customer satisfaction, and safety, as well as reduced greenhouse gas emissions, logistics costs, errors, and repetitive tasks. This study contributes to the field of Administration by critically reflecting on how the application of technological innovations can contribute to PSLs in developing a sustainable strategy, considering the complexity, challenges, and characteristics of these companies. For practical applications, this research provides valuable information for logistics managers and leaders who wish to implement Logistics 4.0 technologies and achieve sustainable benefits. It is worth highlighting that the originality of this study lies in the development of a framework based on empirical data that reveals the applications, benefits, and challenges in adopting Logistics 4.0 to create sustainable value in PSLs.
Logistics 4.0 and Sustainability: Analysis of Practices, Benefits, and Challenges in Logistics Service Providers
Keywords: Logística inteligente; Smart logistics; Digital innovations; Logistics Service Providers; Industry 4.0; Sustainable Supply Chain; Sustainable Development; Inovações digitais; Prestadores de Serviços Logísticos; Indústria 4.0; Cadeia de Suprimentos Sustentáveis; Desenvolvimento Sustentável; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS::ADMINISTRACAO DA PRODUCAO